Liquid Metals 2021
DOI: 10.5772/intechopen.97205
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Experimental Study of Melt Pool Flow Dynamics in Laser Material Processing

Abstract: Laser material processing has becoming a rapid developing technology due to the flexibility of laser tool. Melt pool is the main product from the interaction between laser and material and its features has a great impact on the heat transfer, solidification behavior, and defects formation. Thus, understanding changes to melt pool flow is essential to obtain good fabricated product. This chapter presents a review of the experimental studies on melt pool flow dynamics for laser welding and laser additive manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…EDS analysis indicated that the segregation areas exhibited a high nickel content. This segregation phenomenon can be attributed to the complex flow dynamics within the melt pool, driven by forces such as Marangoni, buoyancy, gravity, and recoil pressure [58]. Elemental segregation in additively manufactured samples can significantly influence corrosion resistance [59].…”
Section: Discussionmentioning
confidence: 99%
“…EDS analysis indicated that the segregation areas exhibited a high nickel content. This segregation phenomenon can be attributed to the complex flow dynamics within the melt pool, driven by forces such as Marangoni, buoyancy, gravity, and recoil pressure [58]. Elemental segregation in additively manufactured samples can significantly influence corrosion resistance [59].…”
Section: Discussionmentioning
confidence: 99%
“…The primary result of the interaction between the laser and materials is the formation of a melt pool. Understanding the characteristics of the melt pool is crucial for achieving high-quality products [52]. Cunningham et al [53] utilized synchrotron X-ray imaging to reveal the sequence of keyhole formation in PBF-LB for metal additive manufacturing, based on laser power density.…”
Section: Melt Pool Dynamicsmentioning
confidence: 99%
“…During the solidification of the melt pool, the centre of the melt pool experienced the maximum temperature, followed by a radial drop, causing a difference in the melt pool surface tension, which led to rounded peaks due to the outward flow of the melt pool. 25…”
Section: Effect Of Lp/ss On Kurtosis and Skewnessmentioning
confidence: 99%